Teknik Pemeliharaan Benih Rajungan (Portunus pelagicus Linn.) Di Balai Besar Pengembangan Budidaya Air Payau Jepara Kabupaten Jepara Propinsi Jawa Tengah [Rearing Technique Of Blue Swimming Crab (Portunus pelagicus Linn.) Fry At Brackish Water Culture Development Centre Of Jepara, Jepara Regency And Central Java Province] - Laksmi Sulwartiwi; Juwita Tri Hermawar Yus (Jurnal Ilmiah Perikanan dan Kelautan, 2010)
AbstractBlue swimming crab is one of fishery commodity for export that still depend from captured, so it will affect population in wild. One of effort to prevent of crab exinction by hatchery advanced. Inhibition of blue swimming crab was survival rate that low, so it was needed case study about rearing technique of blue swimming crab fry. The aim of this case study was to know directly about rearing technique of blue swimming crab fry and problem that emerged in rearing of blue swimming crab fry. This case study was done at Brackish water Culture Development Center of Jepara, Jepara Regency and Central Java of Province on August 1-30, 2005. Work method which used in case study was descriptive by data collection consisted primary and secondary data. Collection data were done by active participation, interview, observation and study literature. Fry was produced from brood stock of egg maturation stage III which came from wild. Activities of rearing fry consisted preparing of rearing pond, stocking density, food feeding, monitoring of water qualities, pest and disease ocontrol and also harvesting. Water qualities measured were salinity 28-32 ppt and water temperature 29-32C. stocking densities were >100 inds/lt with survival rates were 1,3-3,8%. During rearing, fry was given natural feeds such as Chlorella vulgaris, Brachionus plicatilis, Artemia salina, commercial food merk Frippak and grinding shrimp. In this rearing was found red fungi and controlled by using Erythromycin 1ppm. Harvesting was done after fry 18-days age and was done stocking in nursery pond at Brackish water Culture Development Center of Jepara. Conclusion of this case study were rearing technique of blue swimming crab fry consisted brood stock maintenance, fry rearing system, stocking density, monitoring of water qualities, pest and disease control and also harvesting. Challenge in blue swimming crab with steady system were greatly density, plankton die-off, red fungi and also cannibalism that caused blue swimming crab mortalities.